ANALISIS METODE ANTREAN DAN SIMULASI MONTE CARLO PADA ANTREAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DISDUKCAPIL) KOTA SALATIGA DILENGKAPI GUI-R - Diyah Rahayu Ningsih; Sugito Sugito; Agus Rusgiyono (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2022)
One of the services that often occurs in everyday life is the queue service. Queues can arise due to delays in a service system in providing a service, resulting in a row of a group of people to get a service. The queue analyzed in this study is a queue in The Salatiga City Disdukcapil. The parameters on which this research is based are the number of arrivals (λ) and service time (μ) of visitors who arrive. The methods used are queue analysis and Monte Carlo simulation. The Monte Carlo method provides more effective results at each counter than using queue analysis. The result of this study is a decrease in the utilization rate of service facilities, so that it is accompanied by a decrease in the size of system performance for the calculation of Lq, Ls, Wq, and Ws. Decreases in utilization rates and system performance measures at each counter make an increase in the probability of idle systems at each counter. The model generated by the sample data with the Monte Carlo simulation data tends to be the same, namely for counter 1,2,3,4, counter 5 model (G/G/c):(GD/¥/¥), and for counter 6 with queuing model ( G/M/1):(GD/¥/¥).